An Exploratory Study of Film-Induced Tourism in China: a Case of the TV series the Legend of the Condor Heroes and its Film Locations in Peach Blossom Island - Liu, Qianqian (2011)
This dissertation considers the nature and scope of the effect of television-induced tourism on a destination with sparse population, high quality of environment, but limited accommodation capacity and infrastructure. Researches concerning the real and potential, extent and longevity of the effect of the certain case The Legend of the Condor Heroes on Peach Blossom Island, as well as the influence on the visitor travel decision and destination image, were conducted by means of both qualitative unstructured interview and quantitative survey. Questionnaires were designed to obtain the actual and perceived changes in business activity and performance of tourism-related businesses in the island, the effectiveness of The Legend of the Condor Heroes effect on travel decision and the perceived destination image from the perspectives of visitors and business operators, while some individual insights of the effect of the television series on the island were collected from key informant face-to-face interviews. The findings indicated that The Legend of the Condor Heroes tourism did generate benefits to tourism industry in the island, and it was verified that The Legend of the Condor Heroes is long-lasting, having positive impact on the destination image and affecting the visitors’ travel intention to some degree. Besides, another finding in this study was that government effort is a significantly effective contributor to the success of The Legend of the Condor Heroes tourism. Some implication in terms of destination management and marketing were given, which may be of interest to Destination Management/Marketing Organization in the island.